(untitled) (Annals of Medical Research, 2021)
Aim: The objective of this study was to investigate the rate of neural tube defects (NTD) and the clinical features of newborns of mothers who did not use folic acid (FA) in their pregnancies.Material and methods: The data of a total of 82 newborns, who were diagnosed with meningomyelocele were operated and examined, retrospectively. The newborns were divided into two groups depending on whether their mothers used FA during pregnancy or not. Results: The mothers of 37 (45.1%) newborns used FA during the antenatal period, whereas those of 45 (54.9%) newborns did not.The mean birth weight of the newborns whose mothers did not use FA were lower. Furthermore 9 (25%) newborns whose mothers did not use FA were delivered via cesarean section.The incidence of meningomyelocele was 80% for 45 newborns with NTDs whose mothers did not use FA.Conclusion: Our results revealed that the mean birth weight was lower while the incidence of meningomyelocele was significantly higher in newborn infants whose mothers did not use FA.Keywords: Folic Acid; Pregnancy; Meningomyolocele; Spina Bifida.